Identification of Novel Vaccine Candidates against Campylobacter through Reverse Vaccinology. (16th June 2016) - Meunier, Marine; Guyard-Nicodème, Muriel; Hirchaud, Edouard; Parra, Alberto; Chemaly, Marianne; Dory, Daniel
Abstract : Campylobacteriosis is the most prevalent bacterial foodborne gastroenteritis affecting humans in the European Union. Human cases are mainly due to Campylobacter jejuni or Campylobacter coli, and contamination is associated with the handling and/or consumption of poultry meat. In fact, poultry constitutes the bacteria's main reservoir. A promising way of decreasing the incidence of campylobacteriosis in humans would be to decrease avian colonization. Poultry vaccination is of potential for this purpose. However, despite many studies, there is currently no vaccine available on the market to reduce the intestinal Campylobacter load in chickens. It is essential to identify and characterize new vaccine antigens. This study applied the reverse vaccinology approach to detect new vaccine candidates. The main criteria used to select immune proteins were localization, antigenicity, and number of B-epitopes. Fourteen proteins were identified as potential vaccine antigens. In vitro and in vivo experiments now need to be performed to validate the immune and protective power of these newly identified antigens.